let x caught x fishes. y caught x/5 fishes.
x+x/5=36
6x/5=36
x= 36*5/6
x=30
x caught 30 fishes
y caught 6 fishes
2007-01-20 01:17:36
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
It so simple
let the number of fish caught by x be 5y
5y+y=36
6y=36
y=6
y caught 6 fish out of 36
2007-01-20 09:18:16
·
answer #2
·
answered by SOAD_ROX 2
·
0⤊
0⤋
ok the easyest way to do this is remember the ratio between x and y which obviously is 5:1
now this means that y got 1 of every 6 fish court.
if 36 fish were court that means that y got 6 fish because 36/6=6
2007-01-20 10:06:04
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Let the total number of fish caught be 6a.
X caught 5a fishes.
Y caught a fishes.
6a=36
a= 36/6
= 6
Y = a
= 6
2007-01-20 09:22:19
·
answer #4
·
answered by 22127 1
·
0⤊
0⤋
You have two equations - write the given information in numerical data. 1) x + y = 36 and 2) x = 5y
*Since the x-variable is isolated in the 2nd equation...
First:replace "5y" with "x" in the 1st equation...
5y + y = 36
*Combine "like" terms...
6y = 36
*solve for "y" by isolating it on one side > divide both sides by 6...
6y/6 = 36/6
y = 6
"Y" caught 6 fish.
2007-01-20 13:22:11
·
answer #5
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
X+Y=36
5Y=X
So Y=X/5
and X=36-Y
So Y=(36-Y)/5
then 5Y=36-Y
Y=36/6=6
Y caught 6 fish
2007-01-20 09:13:59
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
x + 5x = 36
6x = 36
x = 36/6
x = 6
Y caught 6; x caught 30...5 times 6
2007-01-20 10:53:30
·
answer #7
·
answered by R M 2
·
0⤊
0⤋
total fish caught=36
X caught 5 times as many as Y.
therefore X=5Y
according to question,
X+Y=36
substitute value of Xfrom above
equation becomes
5Y+Y=36
6Y=36
Y=6
THEREFORE NUMBER OF FISH CAUGHT BY Y ARE 6.
2007-01-20 12:05:08
·
answer #8
·
answered by akshit 1
·
0⤊
0⤋
let the number of fishes Y caught be A.
Therefore, X caught 5A fishes.
6A = 36
A = 6
Hence, Y caught 6 fishes
2007-01-20 11:33:35
·
answer #9
·
answered by lwyenin 2
·
0⤊
0⤋
1/2 of 36 is 18. 18x5=90. 90 is the answer
2007-01-20 09:15:01
·
answer #10
·
answered by Yafooey! 5
·
0⤊
1⤋